Environmental Policy, Public Health and Human Rights: Assessing the Regional Regulation on Waste - Toar Neman Palilingan; Donna Okthalia Setiabudhi; Toar K.R. Palilingan (Faculty of Law, Hasanuddin University, 2018)
Everyone has the right to a good and healthy environment as part of human rights. Hence, to actualize the right to a good and healthy environment, the community or everyone has the right to environmental information related to the role in environmental management. The research is a socio-juridical. The results show that the management of human environment in Manado is implemented through the establishment and implementation of local regulations. The issuance of local regulations related to environmental law enforcement are local regulations on Environmental Protection and Management; Domestic Wastewater Management; and Waste Management and Cleaning Service Fees. However, the three local regulations have not been implemented optimally. Even the local regulation on the Waste Management and Cleaning Service Fees provides regulations that are not in accordance with the needs of the community in waste management and not in accordance with the laws and regulations related to waste.